2022
DOI: 10.21037/cdt-22-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparing patient outcomes following minimally invasive coronary artery bypass grafting surgery vs. coronary artery bypass grafting: a single-center retrospective cohort study

Abstract: Background: This present research was designed for comparing coronary artery disease (CAD) patient outcomes following minimally invasive coronary artery bypass grafting surgery (MICS) or coronary artery bypass grafting (CABG).Methods: From 2014-2017, 679 CAD patients underwent MICS (n=281) or CABG (n=398) and were evaluated for the present study. Patient data were analyzed using 1:1 propensity score-matched assessment and a multivariate Cox proportional hazards regression model, and primary study achievements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Additionally, MICS CABG patients experienced no deep wound infection compared to the 6 (4.0%) OPCAB patients who did. Similar wound infection rates have been consistently observed in the literature [17,41] .…”
Section: Early Outcomessupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, MICS CABG patients experienced no deep wound infection compared to the 6 (4.0%) OPCAB patients who did. Similar wound infection rates have been consistently observed in the literature [17,41] .…”
Section: Early Outcomessupporting
confidence: 89%
“…Liang et al compared the early outcomes between multivessel coronary bypass grafting by a sternotomy or a mini-thoracotomy in a retrospective single-center study [41] . From January 2017 to January 2020, 211 patients underwent MICS CABG and 371 underwent conventional OPCAB.…”
Section: Early Outcomesmentioning
confidence: 99%
“…However, McGinn et al 25 demonstrated complete revascularization in 95% of patients that received MICS-CABG. Lapierre et al 41 achieved complete revascularization in all patients regardless of MICS-CABG or OPCAB, and Liang et al 43 demonstrates no significant differences in repeat revascularization in conventional CABG vs MICS-CABG. Despite the excellent short-term results, data regarding longterm follow-up is relatively scarce.…”
Section: Mics-cab Versus Conventional Cabg For Multivessel Diseasementioning
confidence: 97%
“…Being predominantly an off-pump procedure, MICS-CABG offers the advantage of avoiding or minimizing aortic clamping and manipulation, which are known to correlate with perioperative neurological complications. 42 Nevertheless, Liang et al 43 showed no significant differences in rates of stroke between conventional and MICS-CABG; therefore, further investigation might be needed.…”
Section: Mics-cab Versus Conventional Cabg For Multivessel Diseasementioning
confidence: 97%
“…Intraoperative transfusion and hybrid revascularization are especially interesting because both are potentially modifiable. A study from Beijing performed a propensity matched comparison of 281 MICS coronary patients to 398 full sternotomy coronary surgery patients and found similar MACCE and survival at four years [15]. In another retrospective study, the 5-year survival of 88 low risk patients who had undergone minimally invasive direct coronary artery bypass (MIDCAB) was statistically similar to a subgroup of the general Swiss population matched only for gender and age [16 & ].…”
Section: -7907mentioning
confidence: 99%